Perfusion and Insufflation Technique for Preservation of the Stomach and Intestine of a Large White Yorkshire Pig (Sus scrofa domesticus) - Kishore, P.V.S. (Indian Journal of Veterinary Anatomy, 2019)
A perfusion and insufflation technique was used to preserve the stomach and intestine destined for disposal from a humanely slaughtered Large White Yorkshire pig. It serves as a valuable specimen with in situ shape for teaching veterinary anatomy and as an alternative to procuring the organs from a sacrificed and embalmed healthy animal. A pliable hose pipe of suitable size was inserted through the oesophagus and the contents from the recovered stomach and intestine were flushed out through the rectum with water using a variable speed cadaver injector. Perfusion of 10% formalin into the lumen of the stomach and intestine was done through the same hose pipe. The oesophageal and the rectal ends were clamped initially and later tied after complete perfusion. The perfused specimen was immersed in 10% formalin and preserved for a week till complete fixation was ensured. The knots at the tied ends were removed and the perfused formalin was drained out. Insufflation of air was done into the lumen of the stomach and intestine using an air pressure pump after tying the rectal end. After the stomach and intestine were fully inflated the oesophageal end was also tied enabling the specimen ready for use in a life-like condition by storing it in a freezer/cooler, thus avoiding wet formalin storage.